(untitled) (Research, Society and Development, 2021)
This article analyzes the main conceptual categories that guide intersectoral action based on the authors empirical experience compared to the literature on the subject. The text is organized as a glossary and presents thirteen terms: agenda, intersectoral collaboration, conflict, governance, collaborative governance, individual, support mechanism, management model, partnership, communication process, sector, sustainability, territory. These concepts enabled the development of a model of the dimensions of intersectoral collaboration: political dimension, technical dimension, and interaction dimension. They are interrelated and produce integration and support mechanisms for intersectoral collaboration. This theoretical contribution aims to promote a better understanding of intersectoral practice facilitating the choice of this approach in the development of public social policies. Additionally, the covered concepts may contribute to the design of research in the area. The definitions and reflections confirm the complexity of intersectoral collaboration and the importance of seeking support in different knowledge fields for its construction and effectiveness as a practice that generates equity and social justice.